2005
DOI: 10.1099/jmm.0.45799-0
|View full text |Cite
|
Sign up to set email alerts
|

Detection of binary-toxin genes (cdtA and cdtB) among Clostridium difficile strains isolated from patients with C. difficile-associated diarrhoea (CDAD) in Poland

Abstract: Clostridium difficile A þ B þ and A À B þ strains isolated from stool samples of patients with C. difficileassociated diarrhoea (CDAD) were selected from the University Hospital Warsaw collection. The binary-toxin genes cdtA and cdtB were detected by PCR in five of the 41 A þ B þ strains tested, but in none of the 17 A À B þ strains tested, giving 8 . 6 % prevalence (5/58) of binary-toxin-positive strains. All of the strains that were positive for binary-toxin genes were grouped into toxinotype IV, suggesting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
24
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 32 publications
0
24
0
Order By: Relevance
“…Earlier studies have reported a prevalence of CDT of up to 12% (14,40,42), but more recent studies have reported higher numbers consistent with the dissemination of ribotype 027/NAP1 (15,34). Whether this is associated with changes in severity of disease is unclear, although CDT-containing strains have been reported to be associated with more serious disease (3).…”
Section: Discussionmentioning
confidence: 92%
“…Earlier studies have reported a prevalence of CDT of up to 12% (14,40,42), but more recent studies have reported higher numbers consistent with the dissemination of ribotype 027/NAP1 (15,34). Whether this is associated with changes in severity of disease is unclear, although CDT-containing strains have been reported to be associated with more serious disease (3).…”
Section: Discussionmentioning
confidence: 92%
“…Up to 2 % of C. difficile produce only binary toxin and 4-12 % of C. difficile isolates are positive for the toxin Stubbs et al, 2000). The prevalence of binary toxin genes in both toxigenic and non-toxigenic C. difficile strains has been reported from various countries, such as the USA (0.2 %) , Spain (4.5 %) (Alonso et al, 2005) and Poland (8.6 %) (Pituch et al, 2005). During a hospital outbreak of CDI in Pittsburgh, USA, up to 65 % of the clinically recovered C. difficile isolates had binary toxin genes (McEllistrem et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Genes encoding TcdA, an enterotoxin, and TcdB, a cytotoxin, are both located within the pathogenicity locus and are both diverse, while the binary toxin CDT is located elsewhere on the chromosome. Most strains synthesize only TcdA and less frequently TcdB, but some of these also synthesize CDT, whose role in the disease symptoms is still unclear (52,55). In the diagnosis and typing of C. difficile, culture techniques are seldom used, which may result in underestimating the detection of this organism (19).…”
mentioning
confidence: 99%
“…In the diagnosis and typing of C. difficile, culture techniques are seldom used, which may result in underestimating the detection of this organism (19). Instead, several immunological (2,8,65,66) and PCR-based methods, including those directed at identifying and in some cases quantifying the tcdA and tcdB genes and the cdtA and cdtB genes, encoding TcdA and TcdB or CDT, respectively, in stool samples, have been described (6,22,38,52).…”
mentioning
confidence: 99%
See 1 more Smart Citation